Reforming the World Bank twenty years of trial -- and error - Phillips, David A. 1946- (Cambridge University Press, 2009)
In the many studies of the World Bank, a critical issue has been missed. While writers have looked at the Bank's political economy, lending, conditions, advice, ownership and accounting for issues such as the environment, this study looks at the Bank as an organization - whether it is set up to do the job it is supposed to do and, if not, what should be done about it. This book is about the problems of organization and reorganization as much as it is about the problems of assisting third-world development, and it is a case study in flawed organizational reform as much as a critique of the way development assistance is managed. It covers the period that starts at the time of the first major reorganization, in 1987 under President Barber Conable, and ends at the time of the resignation of Paul Wolfowitz, in 2007, but it focuses especially on what happened during the tenure of James Wolfensohn